Onion yield as a function of soil tillage system and soil water content - Feitosa,Jardênia R. (2020)
ABSTRACT Excessive tillage operations under inadequate conditions can raise the cost of agricultural production and lead to soil degradation without adequate crop response. The objective of this study was to evaluate the onion crop response to soil water contents and tillage systems. Three tillage systems were evaluated: P1 (plowing + two harrowings + two seedbed raising operations), P2 (two harrowings + one seedbed raising operation), P3 (one harrowing + one seedbed raising operation); and four soil water contents: 12, 15, 23 and 26%. The experiment was conducted in the irrigated perimeter of Tourão, Juazeiro, BA, Brazil (9° 24’ 7.3” S; 40° 26’ 8.7” W and altitude of 368 m), in 2017, and was installed in split plots, in a randomized block design, with four repetitions. Water contents were arranged in the plots and tillage systems in the subplots. Crop response to the applied treatments was evaluated through the determination of the emergence speed index of the seedlings, regularity of the longitudinal distribution of seedlings, final stand, total and marketable yields of the crop and yield per bulb transverse diameter class. The variation of soil water content had a quadratic effect on the variables emergence speed index, final stand and total onion yield. The treatments did not significantly affect the longitudinal distribution of plants and marketable yield. The tillage system composed of one harrowing and one seedbed raising operation showed to be the most appropriate for onion cultivation by direct seeding.